Vocational Career Choice in Middle Childhood - Ningsih, Mirna Purnama; Barliana, Mokh. Syaom; Widiaty, Isma; Aryanti, Tutin (INVOTEC, 2021)
Career   choice   can   be   made from   an   early   age   through introduction, habituation, and stimulation of children's interests. Parents need to recognize their child's interests related to future career choice. The study  was conducted  on 106 children aged 6-12  years  to  determine  the  careerchoices  of  children.  Data collection  was  carried  out  by  distributing  online  questionnaires (Googleform). Limited interviews were conducted with 5 mothers and  children  to  explore  children's  career  choices.  The  findings on gender show that boys tend to choose career specifics such as  policemen,  military  troops  and  businessmen. On  the  other hand, girls tend to choose career specifics such as doctors and teachers.  Career  choice  in  children  is  influenced  by  3  (three) factors, namely (1) the desire in the child, (2) interests/hobbies, (3) the profession of parents and family (role models)